A new flightless trechodine genus and species from the South African Cape region (Coleoptera: Carabidae: Trechitae) - Geginat, Gernot (Zootaxa, 2006)
Scaurotrechodes capensis gen.nov., sp.nov. is described from the Cape province. It is the first endemic flightless representative of the tribe Trechodini from southern Africa.